Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/bpo.0000000000001521
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of the AOSpine Thoracolumbar Classification System in Children: Results of a Multicenter Study

Abstract: Background: The purpose of this study was to determine whether the new AOSpine thoracolumbar spine injury classification system is reliable and reproducible when applied to the pediatric population. Methods: Nine POSNA (Pediatric Orthopaedic Society of North America) member surgeons were sent educational videos and schematic papers describing the AOSpine thoracolumbar spine injury classification system. The material also contained magnetic resonance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“… 14 , 18 , 19 When evaluating the AOSpine Thoracolumbar Spine Injury Classification System in children, using a single country cohort of observers and the same patient series as this study, the results demonstrated high interobserver reliability of 82% ( k F = 0.82; 95% CI 0.77 to 0.87) and intraobserver reproducibility of 81% ( k F = 0.81; 95% CI 0.71 to 0.90). 10 The results of this study using an international group of observers are comparable, with interobserver reliability of 74% (kF = 0.74; 95% CI 0.71 to 0.78) and intraobserver reliability of 91% (kF = 0.91; 95% CI 0.83 to 0.99). Given the diverse group of global reviewers with different patient populations and educational backgrounds, the results of this study further strengthen the applicability of the AOSpine Thoracolumbar Spine Injury Classification System in the paediatric population.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“… 14 , 18 , 19 When evaluating the AOSpine Thoracolumbar Spine Injury Classification System in children, using a single country cohort of observers and the same patient series as this study, the results demonstrated high interobserver reliability of 82% ( k F = 0.82; 95% CI 0.77 to 0.87) and intraobserver reproducibility of 81% ( k F = 0.81; 95% CI 0.71 to 0.90). 10 The results of this study using an international group of observers are comparable, with interobserver reliability of 74% (kF = 0.74; 95% CI 0.71 to 0.78) and intraobserver reliability of 91% (kF = 0.91; 95% CI 0.83 to 0.99). Given the diverse group of global reviewers with different patient populations and educational backgrounds, the results of this study further strengthen the applicability of the AOSpine Thoracolumbar Spine Injury Classification System in the paediatric population.…”
Section: Discussionsupporting
confidence: 54%
“…Similar to a previous single country cohort of observers, the results of this study incorporating an global cohort of observers show high interobserver reliability and interobserver reproducibility when applying the AOSpine Thoracolumbar Spine Injury Classification System to the paediatric population. 10 Additionally, these results are strengthened with the diverse group comprising the study observers. Further studies are needed to determine the transferability of the AOSpine Thoracolumbar Spine Injury Classification System in the other anatomical regions of the spine, which are currently underway.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, an 81% accuracy for across-theboard RadBot reading of lumbar spine MRI scans obtained in our feasibility study is approximately 15% higher than the published interobserver and intraobserver reliability rates obtained on routine reports provided by radiologists on the same scan. [91][92][93][94][95][96][97][98][99] Despite these limitations, the RadBot was able to give the printed MRI report in approximately 8 to 10 minutes, which in today's health care cost-savings context may save time and prevent overuse owing to improved reporting standards. Future studies will have to demonstrate the reliability of the RadBot readings with j analysis of agreement between the RadBot and the MRI reports provided by a radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study validated the use of the Upper Cervical Section, called the Upper Cervical Classification System (UCCS), in the adult population, assessing both inter-rater and intra-rater reliability 15. A previous study conducted by the same authors of this paper validated the Thoracolumbar System in the pediatric population 22. The UCCS integrates the location of the injury (Occipitocondyle/Craniocervical Joint, C1 Ring and C1-C2 joint, C2 and C2-3 joint), evidence of ligamentous injury, neurological status, and patient-specific modifiers 15.…”
mentioning
confidence: 86%